Vitamin D deficiency and morbidity among preterm infants in a developing country - Srinivasan, Nitin; Chandramathi, Jayasree; Prabhu, Aswin S.; Ponthenkandath, Sasidharan (International Journal of Contemporary Pediatrics, 2017)
Background: The association of serum vitamin D levels to clinical outcome in VLBW infants has not been studied. Our objective was to measure the cord blood levels, and the dose response for two doses of vitamin D in preterm infants and correlate the relationship of vitamin D levels to the clinical outcome. Methods: We prospectively obtained cord blood levels in 80 preterm infants under 34 weeks gestation (mean gestation age 29±2 weeks and BW: 1210±350 gms). Infants were supplemented with 400 IU or 800-1000 IU vitamin D daily. Serun vitamin D levels were obtained at 2 - 3 weeks after supplementation and levels were correlated to clinical outcome. Results: The mean cord blood vitamin D level was 12±8.5 ng/ml. Babies who developed sepsis and compared to those who did not develop these morbidities, ROP had vitamin D levels: 13.5±6 (ng/ml) versus 30.5±10 (ng/ml) (p < 0.01) and 15.7±11 (ng/ml) versus 34±18 (ng/ml) (p <0.03) respectively. Supplementation with 400 IU vitamin D resulted in levels of 17±8.6 (ng/ml) and infants given 800-1000 IU vitamin D had levels 46±17(ng/ml) (p <0.001). Conclusions: These data suggest that cord blood vitamin D levels are low in preterm infants and 800-1000 IU vitamin D supplementation is advisable to achieve levels >30 ng/ml. Infants with low levels of vitamin D have higher incidence of sepsis, and ROP.